Sieci dostaw w modelach ewolucji łańcuchów dostaw - Szymczak, Maciej (Supply Nets in the Supply Chain Maturity Models, 2005)
This paper discusses the process of developing supply nets according to the most popular supply chain maturity models. These models indicate important aspects of this multistage process that are pointed out herein.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 166-172